2016
DOI: 10.1063/1.4947273
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of the lifetime of guided discharges triggered in atmospheric air by femtosecond laser filaments up to 130 μs

Abstract: Abstract:The triggering and guiding of electric discharges produced in atmospheric air by a compact 100 kV Marx generator is realized in laboratory using an intense femtosecond laser pulse undergoing filamentation. We describe here an approach allowing extending the lifetime of the discharges by injecting a current with an additional circuit. Laser guiding discharges with a length of 8.5 cm and duration of 130 µs were obtained.In the last decade femtosecond laser filaments has proved to be a powerful tool to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Recent works succeeded to increase the laser-produced plasma lifetime up to few microseconds by using an external electric field from a 50 kV DC high-voltage source19. In addition, other work recently reported an increase of the laser-guided discharge lifetime up to 130  μ s by inserting inductances on a 100 kV Marx generator20.…”
mentioning
confidence: 99%
“…Recent works succeeded to increase the laser-produced plasma lifetime up to few microseconds by using an external electric field from a 50 kV DC high-voltage source19. In addition, other work recently reported an increase of the laser-guided discharge lifetime up to 130  μ s by inserting inductances on a 100 kV Marx generator20.…”
mentioning
confidence: 99%
“…The generation of millisecond-duration, 100 A sparks was done using a slightly modified version of the double-circuit scheme already used by Arantchouk et al . 25 . This scheme was built around a filamentation-triggered Marx generator as the high-voltage source.…”
Section: Resultsmentioning
confidence: 99%
“…also demonstrated control of curved spark trajectories by means of Airy laser beams instead of the widely used Gaussian beam 24 . Théberge and co-authors also showed that meter-sized, milliseconds duration guided discharges can successfully be developed using a double-circuit scheme 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Using this with (7), the circuit parameters may be estimated using L, (8)(9)(10)(11), and the fit parameters α i and ω i as…”
Section: Estimating Time-dependent Circuit Parametersmentioning
confidence: 99%
“…Such modified Marx generators are shown to tolerate circuit-parameter changes more than Tesla transformers, making them attractive alternatives to Tesla transformers in the applications mentioned above. While compact, 13 high-repetition, 14 and inductively loaded 9 Marx generators and coupled Marx-Tesla circuits 15 exist, this work demonstrates that a modified a) Present address: Facebook, Inc., 1 Hacker Way, Menlo Park, CA 94025, USA Marx generator can mimic a conventional, loosely coupled spark-gap Tesla transformer (SGTT). Fig.…”
mentioning
confidence: 93%